2013
DOI: 10.1097/qai.0000000000000001
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T-Cell Activation Is Associated With Lipodystrophy and Visceral Fat Accumulation in Antiretroviral Therapy–Treated Virologically Suppressed HIV-Infected Patients

Abstract: CD8⁺ T-cell activation was associated with LD and the relative amount of VAT in antiretroviral therapy-controlled, virologically suppressed, HIV-infected patients. We propose that CD8 activation may be involved in the accumulation of central fat frequently observed in these patients, with resulting increased cardiometabolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…CD8+ T-cell activation is considered a less strong predictor of mortality and non-AIDS defining events in treated HIV infection than soluble immune activation markers [35, 36]. However, it has been associated with certain non-AIDS comorbidities, such as visceral fat accumulation and subclinical carotid artery disease [37, 38]. Our findings, though preliminary and obtained in a small group of patients, suggest that decreased T-cell activation might contribute to mediate exercise-induced health benefit.…”
Section: Discussionmentioning
confidence: 99%
“…CD8+ T-cell activation is considered a less strong predictor of mortality and non-AIDS defining events in treated HIV infection than soluble immune activation markers [35, 36]. However, it has been associated with certain non-AIDS comorbidities, such as visceral fat accumulation and subclinical carotid artery disease [37, 38]. Our findings, though preliminary and obtained in a small group of patients, suggest that decreased T-cell activation might contribute to mediate exercise-induced health benefit.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies which have suggested that peripheral fat loss is mainly affected by HIV immune dysregulation, specifically high levels of CD8 + T-cell activation. 5,8 …”
Section: Discussionmentioning
confidence: 99%
“…HIV-associated chronic inflammation and immune activation may play a role in the development of visceral adiposity, with circulating CD8 + T lymphocyte activation linked to VAT accumulation[53]. Activation of the renin-angiotensin system has been independently associated with treated HIV infection and VAT accumulation[54, 55], and appears to independently predict insulin resistance[56].…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%